Factors Affecting Influencer Marketing Vs Social Media - An Empirical Study (Journal of Pharmaceutical Negative Results, 2023)
The proliferation of the use of social networks has resulted in shifts in the manner in which brands and companies communicate with their target audiences, which are the end users of their products. According to the business publication Forbes, the most prominent trend in marketing at the moment is called influencer marketing. The objective of this paper is to provide an explanation of the idea of influencer marketing in the context of a marketing concept by situating the idea within the context of the digital era and of a world connected by social media. In final result, this section of the paper categorises the factors that influencers have into different types to assist campaign designers in monitoring, examining, and selecting the influencers who are the best fit for a particular campaign and the popularity of a particular company.